Underground Space Planning in Ho Chi Minh City - A Challenge for Urban Governance - Tran Duc Thuan; Vo Nhat Luan; Le Manh Tuong; Huynh Thi Ha (International Journal of Scientific Research in Civil Engineering, 2024)
Underground spaces are used for constructing transportation works, water supply and drainage systems, shelters for the storage of military vehicles, transportation vehicles, diversion tunnels for hydroelectric projects, and large, solid buildings for work, commercial purposes, or national security, etc. Underground spaces have been developed by advanced countries since the mid-18th century. With the strong development of the global economy, underground spaces have been increasingly utilized and continuously expanded to address problems related to transportation, and the lack of technical and social infrastructure. In Vietnam, since the 1930s, the French have built many railway tunnels along the North-South route. After peace was restored, the government gradually invested in building numerous road tunnels (such as Hai Van, Deo Ca, Nui Vung, etc.) and tunnels in urban areas like the Thu Thiem immersed tunnel, Kim Lien tunnel, Thanh Xuan tunnel, etc. However, these are only temporary solutions, and nearly 300 major intersections in Saigon are still at ground level, causing frequent traffic congestion and safety issues, especially during peak hours, because Ho Chi Minh City does not yet have an underground urban space plan. To address the aforementioned issues, it is essential to promptly implement an underground urban space plan for Ho Chi Minh City, which has a population of approximately 13 million people and one million various types of vehicles.